(untitled) (Research, Society and Development, 2025)
Hyaluronic acid injections have become increasingly popular in minimally invasive aesthetic procedures, especially in orofacial harmonization, due to their ability to rejuvenate facial features and restore volume in areas such as the nasolabial folds, lips, and under-eye region. The aim of this narrative literature review is to evaluate amaurosis as an adverse event of HA application in the facial region. The main cause of hyaluronic acid–induced amaurosis is arterial embolization, which occurs when the filler is injected into facial vessels, blocking the ophthalmic artery and restricting blood flow to the retina, potentially leading to irreversible vision loss. The primary mechanism behind this complication is the embolization of filler material, which travels through the circulatory system and obstructs critical arteries supplying blood to the eye. High-risk areas for this type of complication include the glabella, periocular regions, and nose, where anastomoses between the facial and ophthalmic arteries are more prevalent. Several risk factors contribute to the onset of amaurosis, such as inadequate injection technique, excessive pressure, and injection into unsafe anatomical zones. To prevent such complications, professionals must have a deep knowledge of facial anatomy, employ safe injection techniques, and use appropriate devices, such as cannulas instead of needles, to minimize the risk of vascular injury. In addition, the use of local vasoconstrictors, such as epinephrine, and aspiration prior to injection are further safety measures.